Social Facts in the Novel a Woman at Zero by Nawal El Saadawi (A Socio-literary Snalytical Study by Alan Swingwood) - Taufiqurrahman, Taufiqurrahman (CV. Creative Tugu Pena, 2024)
This study aims to reveal some of the facts of life in Egypt in 1975 through the novel Woman at Point Zero by Nawal El Saadawi, using the theory of social literature by Alan Swingwood. The method used by the researcher is the qualitative descriptive approach, in the type of desk research in which all the data collected are Study, process and analyze it completely using literary sources. The approach used by the researcher is a multidisciplinary approach that combines the study of Arabic literature and social science. The results of the research in this study show that the social realities expressed by Nawal through her novels, which are domestic, harassment, sexual violence, economic poverty, and political support, are interconnected and even lead to the continuation of the reality of prostitution as the social reality. In Egypt, Nawal El Saadawi, as the author of the novel Woman at Point Zero, is a great novelist and socialist feminist activist. She had a global vision that she fought for in daily life and through her novels, and because of her global vision, her novel was considered influential in Egyptian society, especially Egyptian women, and women around the world in general. This study includes some research implications. Firstly, this research is expected to provide some description of the reality of life in Egypt, which led to the emergence of prostitution in Egypt. Secondly, it is hoped that this research will provide a complete picture of Nawal El Saadawi’s life and respond to the accusations directed against her. Thirdly, through this study, this research can support the point of view about the power of literary work. Keywords: A Socio-literary, Social Facts Novel, Alan Swingwood